Smartphone Thermography for Lower Extremity Local Flap Perforator Mapping - Pereira, Nicolás; Hallock, Geoffrey G. (Journal of Reconstructive Microsurgery, 2020)
Background The versatile application of local perforator flaps for coverage throughout the lower extremity has already been well proven. Often a “free-style” approach has been used to design these flaps, as conventional imaging devices for perforator identification may be too expensive or unavailable. The recent adaptation of Smartphone thermal digital imaging may now prove to be a cheaper and more readily available means for identifying the requisite perforators that will sustain these local flaps.Methods Over the past year, a prospective study was undertaken of all patients having a local perforator flap for coverage of a lower extremity defect. Twenty-eight local perforator flaps involving all subtypes were utilized in 25 patients. Smartphone thermography was used in all patients preoperatively to identify preferable perforator or vascular network “hot spots” that allowed appropriate flap design. Intraoperative and postoperative monitoring was similarly done for all flaps to determine outcomes.Results All local perforator flaps were based on perforators identified using smartphone thermography. All flaps (23 or 82.1%) that the thermal digital image predicted 100% viability totally survived. Five flaps were predicted to have marginal viability, but two nevertheless survived completely while the others required only minor readjustments. Peninsular and keystone variety perforator flaps were those most commonly used.Thermography always facilitated making the correct decision as to whether a proximal- or distal-based peninsular flap would be superior. Subfascial elevation of cool spots in keystone flaps were found to be least likely to interfere with flap perfusion.Conclusion Smartphone thermography is an inexpensive and expeditious means for identification of “hot spots” that is always used by us to ensure perfusion to lower extremity perforator local flaps. This is a complementary technique for their safer design, harvest, and subsequent monitoring in conjunction with more complex screening tools as indicated.
Keywords: smartphone; thermography; local perforator flap; keystone flap; propeller flap; peninsular flap; island flap